Music Composition Tresna Yana | Komposisi Tabuh Kreasi Tresna Yana - I Made Satria Prawira (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
Tresna Yana is a creative musical work inspired by the stylist's personal experience in a love story. The title Tresna Yana was chosen because Tresna Yana means a journey of love. Everyone has a different love story, and a different love dynamic. Likewise with stylists who experience various feelings and emotions in the love story experienced from the beginning of knowing love until now. The purpose of creating Tresna Yana's work is to express what the stylist feels and the dynamics of love experienced. This work uses the medium of expressing gamelan samapada which has seven notes with the aim of building the desired atmosphere and using vocals to clarify the atmosphere experienced. The creation of this work went through three stages, namely exploration (exploration), experiment (improvisation), and formation (forming). Structurally, this work is divided into four parts where each part has an interrelated relationship. This work is expected to send a moral message about how important the power of holy love is in life.